CUP study: protocol for a comparative analysis of centralised waitlist effectiveness, policies and innovations for connecting unattached patients to primary care providers. Issue 3 (7th March 2022) - Marshall, Emily Gard; Breton, Mylaine; Green, Michael; Edwards, Lynn; Ayn, Caitlyn; Smithman, Mélanie Ann; Ryan Carson, Shannon; Ashcroft, Rachelle; Bayoumi, Imaan; Burge, Frederick; Deslauriers, Véronique; Lawson, Beverley; et al.
Abstract : Introduction: Access to a primary care provider is a key component of high-functioning healthcare systems. In Canada, 15% of patients do not have a regular primary care provider and are classified as 'unattached'. In an effort to link unattached patients with a provider, seven Canadian provinces implemented centralised waitlists (CWLs). The effectiveness of CWLs in attaching patients to regular primary care providers is unknown. Factors influencing CWLs effectiveness, particularly across jurisdictional contexts, have yet to be confirmed. Methods and analysis: A mixed methods case study will be conducted across three Canadian provinces: Ontario, Québec and Nova Scotia. Quantitatively, CWL data will be linked to administrative and provider billing data to assess the rates of patient attachment over time and delay of attachment, stratified by demographics and compared with select indicators of health service utilisation. Qualitative interviews will be conducted with policymakers, patients, and primary care providers to elicit narratives regarding the administration, use, and access of CWLs. An analysis of policy documents will be used to identify contextual factors affecting CWL effectiveness. Stakeholder dialogues will be facilitated to uncover causal pathways and identify strategies for improving patient attachment to primary care. Ethics and dissemination: Approval to conduct this study has been granted in Ontario (Queens University Health Sciences and Affiliated Teaching Hospitals Research Ethics Board, file number 6028052; Western University Health Sciences Research Ethics Board, project 116591; University of Toronto Health Sciences Research Ethics Board, protocol number 40335), Québec (Centre intégré universitaire de santé et de services sociaux de l'Estrie, project number 2020–3446) and Nova Scotia (Nova Scotia Health Research Ethics Board, file number 1024979).